Genetic engineering of psbA gene in Nicotiana tabacum - Hucková, Dagmar (Jihočeská univerzita, 2018)
Transformation vector with mutated psbA gene and selective aadA gene was created and transferred into Nicotiana tabacum living cells using Biolistic bombardment. Due to homologous recombination, transformed plant lineage carrying D1-A209, D1-C-212 instead of D1-S209, D1-S212 in D1 protein in PS II was obtained. Seeds from transformed plant were harvested and homoplasmy of the first generation was tested. These mutations caused higher thermostability in Synechocystis sp. PCC6803 so the transformed plant is expected to be the first step in the study of PS II thermostability in higher plants.
Genetic engineering of psbA gene in Nicotiana tabacum
Keywords: Biolistics; genetic transformation; psbA gene; Biolistics; genetic transformation; psbA gene